Perspective Drawing Techniques with Vision Frame Media: Case Study in Art Learning at Middle School - Tejo, Ian Sigit Ario; Alimuddin, Alimuddin; Mukaddas, Andi Baetal (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Perspective drawing is a fundamental skill in art education that plays a crucial role in developing visual abilities, creativity, and the understanding of three-dimensional space on a two-dimensional plane. However, many students experienced difficulties in grasping the abstract concept of perspective, particularly in determining the horizon line and vanishing points, which was attributed to the limitations of conventional learning media. Therefore, this study examined the application of the Vision Frame learning media in teaching perspective drawing techniques to students at Islamic Middle School. The research employed observation and questionnaire methods to collect data on students' perceptions of the effectiveness of Vision Frame as a visual aid in the perspective drawing learning process. This research was conducted at the Islamic Middle School (SMPIT) Darul Fikri Makassar. The data analysis techniques included both qualitative and quantitative analyses. The analysis revealed that the majority of students (75%) rated Vision Frame as highly effective in accelerating and simplifying the determination of the horizon line and vanishing points. No students provided negative feedback regarding this media. These findings indicated that the use of Vision Frame significantly enhanced students' understanding of perspective concepts, reduced technical errors, and increased their confidence in drawing. Therefore, Vision Frame was considered an innovative and effective learning medium worthy of integration into the art curriculum at the junior high school level, as demonstrated in the case study at SMPIT Darul Fikri Makassar.